2014
DOI: 10.1007/s11665-014-1334-8
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Nitinol-Copper Shape Memory Alloy Bimorph Actuators

Abstract: This study aims to examine the effect of annealing conditions on nitinol (NiTi) characteristics and applies this knowledge to fabricate a NiTi-copper shape memory alloy bimorph actuator. The effect of the annealing conditions was investigated at various temperatures, i.e., 500, 600, and 650°C, for 30 min. With the characterizations using x-ray diffraction, energy dispersive spectroscopy, and differential scanning calorimetry techniques, the results showed that annealing temperatures at 600 and 650°C were able … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
3
12
0
Order By: Relevance
“…Normally, one end of the cantilever will be fixed while the other end will provide displacement upon heating or cooling depending on the SMA properties. Among the latest studies of this kind of actuator is one reported by Wongweerayoot et al [91]. In [91], a 5 μm thick NiTi thin film was deposited on a freestanding copper structure forming a bimorph microgripper.…”
Section: Thin-film Sma Actuatormentioning
confidence: 99%
See 1 more Smart Citation
“…Normally, one end of the cantilever will be fixed while the other end will provide displacement upon heating or cooling depending on the SMA properties. Among the latest studies of this kind of actuator is one reported by Wongweerayoot et al [91]. In [91], a 5 μm thick NiTi thin film was deposited on a freestanding copper structure forming a bimorph microgripper.…”
Section: Thin-film Sma Actuatormentioning
confidence: 99%
“…Among the latest studies of this kind of actuator is one reported by Wongweerayoot et al [91]. In [91], a 5 μm thick NiTi thin film was deposited on a freestanding copper structure forming a bimorph microgripper. According to the report, the microgripper was able to grasp and hold a small plastic ball weighing around 0.5 mg ( Figure 5).…”
Section: Thin-film Sma Actuatormentioning
confidence: 99%
“…Over the years, shape memory alloy (SMA) have such attractive advantages compared to other actuation mechanisms such as high power density, large actuation force, large displacement range, low cost, resistance to corrosion, and biocompatibility [1]. This makes SMA the preferred material to fabricate microactuators in various specific applications [2, 3], such as microgrippers [4, 5], micropumps [6, 7], endovascular surgery [8, 9], and microrobots [10, 11]. However, SMA‐based actuators have often been described as having a slow response speed caused by the low cooling speed of SMA [12], which is seen as a major hindrance for the broad implementation.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of research has been carried out on shape memory alloys recently. Among them, Wongweerayoot et al [2] prepared a NiTi-Cu shape memory alloy bimorph actuator and studied the effect of annealing conditions on nitinol found that Ringer solution proved itself to be most corrosive followed by SBF and HBSS. The corrosion potential also changes in a similar fashion.…”
Section: Introductionmentioning
confidence: 99%